MILK Symposium review: Foodborne diseases from milk and milk products in developing countries—Review of causes and health and economic implications - Grace, Delia; Wu, F.; Havelaar, A.H. (American Dairy Science Association, 2020)
Dairy production is rapidly increasing in developing countries and making significant contributions to health, nutrition, environments, and livelihoods, with the potential for still greater contributions. However, dairy products can also contribute to human disease in many ways, with dairyborne disease likely being the most important. Health risks may be from biological, chemical, physical, or allergenic hazards present in milk and other dairy products. Lacking rigorous evidence on the full burden of foodborne and dairyborne disease in developing countries, we compiled information from different sources to improve our estimates. The most credible evidence on dairyborne disease comes from the World Health Organization initiative on the Global Burden of Foodborne Disease. This suggests that dairy products may has been responsible for 20 disability-adjusted life years per 100,000 people in 2010. This corresponds to around 4% of the global foodborne disease burden and 12% of the animal source food disease burden. Most of this burden falls on low- and middle-income countries (LMIC). However, the estimate is conservative. Weaker evidence from historical burden in high-income countries, outbreak reports from LMIC and high-income countries, and quantitative microbial risk assessment suggest that the real burden may be higher. The economic burden in terms of lost human capital is at least US$4 billion/yr in LMIC. Among the most important hazards are Mycobacterium bovis, Campylobacter spp., and non-typhoidal Salmonella enterica. The known burden of chemical hazards is lower but also more uncertain. Important chemical hazards are mycotoxins, dioxins, and heavy metals. Some interventions have been shown to have unintended and unwanted consequences, so formative research and rigorous evaluation should accompany interventions. For example, there are many documented cases in which women's control over livestock is diminished with increasing commercialization. Dairy co-operatives have had mixed success, often incurring governance and institutional challenges. More recently, there has been interest in working with the informal sector. New technologies offer new opportunities for sustainable dairy development.